Antimicrobial Effect of Leaves of Phyllanthus niruri and Solanum nigrum on Caries Causing Bacteria: An In vitro Study - J sunitha; Swathy Krishna; R Ananthalakshmi; J Sathiya Jeeva; AS Smiline Girija; Nadeem Jeddy (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Solanum nigrum and Phyllanthus niruri are common herbs which are indigeneous to India. Solanum nigrum commonly called ‘manathakkali Keerai’ in Tamil, forms an indispensable part of South Indian diet. Phyllanthus niruri (keezhanelli in Tamil) is a widely used medicinal plant, the leaves of which have been used extensively in Ayurveda and native medicine to cure various liver ailments. The herbs Solanum nigrum and Phyllanthus niruri have been found to be effective against numerous enteropathogens in various in vitro studies. Aim: To assess and compare the antibacterial efficacy of the crude alcoholic extract of the leaves of Solanum nigrum and Phyllanthus niruri against five cariogenic organisms. Materials and Methods: Standard strains of the microorganisms were obtained from ATCC (American Type Culture Collection) and MTCC (Microbial Type Culture Collection) which comprised of Streptococcus mutans MTCC no. 890, Streptococcus oralis MTCC no 2696, Lactobacillus acidophillus MTCC no. 10307, Streptococcus sanguis ATCC no. 10556 and Streptococcus salivarius ATCC no. 13419. The organisms obtained were revived and lawn cultured on Trypticase Soy Agar-Blood Agar (TSA-BA) and de Man, Rogosa and Sharpe (MRS) agar media. The antibacterial effect of the dried and powdered leaves of Solanum nigrum and Phyllanthus niruri was tested using agar well diffusion method. The zones of inhibition obtained after incubation were measured and tabulated. The antibacterial activity for the two herbs was compared using the Mann-Whitney test. Results: The antibacterial zones of inhibition obtained for the herb Solanum nigrum was in the range of 12.3-14.6 mm and ranged from 9.7-11.6 mm for the herb Phyllanthus niruri. When the zones of inhibition were compared for the herbs, Solanum nigrum showed significantly greater zones of inhibition compared to Phyllanthus niruri for the organisms Streptococcus sanguis, Streptococcus salivarius, Streptococcus oralis and Streptococcus mutans (p-value<0.05). Conclusion: The alcoholic extract of leaves of Solanum nigrum and Phyllanthus niruri showed significant antibacterial activity against cariogenic organisms, with Solanum nigrum being more anti-cariogenic than Phyllanthus niruri.